Private Sector Dialogue on Enhancing the Commercialization and Scaling of Climate-Smart and Modern Agricultural Technologies and Innovations to the Last Mile - Barungi, Julian; Okonya, Joshua; Recha, John W.M.; Radeny, Maren A.O. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The private sector dialogue on enhancing the commercialization and scaling of climate-smart and modern agricultural technologies and innovations to the last mile was held as a side event during the African Conference on Agricultural Technologies (ACAT), which took place at the Kigali International Convention Center from June 9 to 12, 2025. ACAT brought together over 700 participants from over 35 countries, including the Prime Minister of the Republic of Rwanda, the former President of the Republic of Nigeria, representatives of six African governments including two ministers from Malawi and Ghana, and five ministers from Rwanda, farmers, 160 youths, heads of international, continental and country level agencies, researchers, private sector players including financial institutions and industry experts to discuss next generation agricultural technology solutions for Africa's farmers. The private sector dialogue discussed: (i) key bottlenecks and barriers that hinder the commercialization of climate resilient agricultural technologies and innovations by private companies and solutions; (ii) emerging opportunities for private companies to scale climate resilient agricultural technologies and innovations; (iii) challenges in the policy environment in which agricultural private sector actors operate; and (iv) strategies for strengthening regional and national private sector forums involved in the agriculture sector to scale CSA technologies and innovations. The private sector dialogue was officially opened by the Minister of Agriculture and Animal Resources in Rwanda – Hon. Dr. Mark Cyubahiro Bagabe and was attended by 88 participants (53 male; 35 female) comprising representatives from the private sector, farmer organizations, youth organizations, academia, Ministries of Agriculture, National Agricultural Research Institutes, International Research Organizations, Non-Governmental Organizations, Financial Institutions and Development Partners. The dialogue agreed on the following key issues: (i) strengthening partnerships with the private sector in scaling CSA technologies; (ii) recognizing the critical role of private sector in agri-food systems transformation and agricultural sector development, within policy frameworks including National Development Plans, National Agriculture Investment Plans and implementation of the Kampala CAADP Strategy and Action Plan; (iii) facilitating access to finance by private sector engaged in promoting scaling of CSA technologies; (iv) strengthening collaboration and dialogue among private sector actors in agriculture; and (v) leveraging digital technologies in promoting the use and adoption of CSA technologies.